2021
DOI: 10.5327/z2447-212320212000112
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication use in older adults: prevalence and physician knowledge

Abstract: OBJECTIVE: To analyze the frequency, profile, and additional variables associated with the prescription of potentially inappropriate medications (PIM) to older adults in primary care, and evaluate physicians’ knowledge about these medications. METHODS: A cross-sectional study was conducted based on data from patient records for the period of January 2014 to December 2017 in a city located in the state of Minas Gerais. The frequency of PIM use was evaluated based on the 2019 Beers-Fick criteria. Physician knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…A poor concordance between criteria was found which means there was minimal overlap between the criteria. Several studies have also shown a high PIM prevalence in older adult primary care users, ranging from 23.6 to 75.9% [33][34][35][36][37][38][39]. The Beers criteria are usually the tool that identifies most PIMs in older population when several screening tools are compared to each other [33,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A poor concordance between criteria was found which means there was minimal overlap between the criteria. Several studies have also shown a high PIM prevalence in older adult primary care users, ranging from 23.6 to 75.9% [33][34][35][36][37][38][39]. The Beers criteria are usually the tool that identifies most PIMs in older population when several screening tools are compared to each other [33,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review, the worldwide overall pooled prevalence of PIM use was 36.7%, varying between 47.0% in Africa, 46.9% in South America, 37.2% in Asia, 35.0% in Europe, 29.0% in North America, and 23.6% in Oceania [21]. Moreover, high PIM prevalence could impose a high economic burden on the older population and society [2].…”
Section: Introductionmentioning
confidence: 99%